TRANSFER OF ELECTRIC CHARGE THROUGH Al-Se95Te5-Te STRUCTURE - Atayeva, S. U.; Mehdiyeva, S. I.; Isayev, A. I.; Qaribova, S. N. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
It is established that current passing through Al-Se95Te5<Sm>-Te structures is carried out by monopolar injection mechanism at participation of traps for holes. It is shown that the doping by samarium strongly influences on the current flow mechanism in the investigated structure due to changes in the energy spectrum of the local states.The local level parameters (concentration and energy state) controlling the electric charge transfer are defined with the use of existing theories of injection currents.